Bilateral Cataract Secondary to High-Voltage Electrical Burn: Case Report and Literature Review - Orozco-Juarez, Karla; Thomassiny-Bautista, Gabriela (Revista Médica del Instituto Mexicano del Seguro Social, 2026)
Background: Electrical cataracts are an uncommon but clinically significant consequence of high-voltage injuries. Their onset may occur within weeks or months, and, without timely recognition, they may cause severe visual impairment. Electrical current induces thermal and direct cellular damage to the lens epithelium, leading to accelerated opacification distinct from age-related cataracts. Clinical case: A 52-year-old electrician sustained a 23,000-volt electrical burn during a workplace accident, with the current entering through the left arm and exiting through the facial and cervical regions. Two months later, he developed rapidly progressive bilateral visual loss. Ophthalmologic examination revealed mature cataracts in both eyes, normal intraocular pressure, without ultrasonography evidence of posterior segment abnormalities. Visual evoked potentials demonstrated moderate conduction delay with intact pathways. Bilateral phacoemulsification with intraocular lens implantation was performed, resulting in significant improvement, with visual acuity increasing from hand-motion perception to 20/40. Conclusions: High-voltage trauma can produce rapidly progressive bilateral cataracts even in the absence of retinal or optic nerve injury. Early ophthalmologic evaluation is essential in patients with electrical burns, as timely surgical management allows meaningful visual restoration and prevents long-term disability.